A new zoroasterid asteroid from the Eocene of Seymour Island, Antarctica - Palópolo, Evangelina Elizabeth; Brezina, Soledad Silvana; Casadio, Silvio Alberto; Griffin, Miguel; Santillana, Sergio Nestor (Acta Palaeontologica Polonica)
New, well-preserved fossil starfish material is recorded from the Eocene La Meseta Formation exposed in Seymour Island, Antarctica. The use of new technology (i.e., microCT) on several fragments enabled the visualization of new characters and the differentiation of a new species, Zoroaster marambioensis sp. nov., which was previously identified as Zoroaster aff. Z. fulgens. Diagnostic characters of Z. marambioensis sp. nov. are (i) central disc plate enlarged, lobate and flattened, (ii) disc ring with enlarged, tumid radials and polygonal, flattened inter-radials, (iii) primary spines on disc only present on radials, (iv) oral armature with 1–3 primary spines and 1–2 secondary spines for each prominent adambulacral. The depositional setting represents the outer zone of an estuary dominated by marine processes affected by long lived hyperpycnal flows. We argue that zoroasterids colonized a distal part of the estuary under normal marine salinity and were killed by the input of freshwater carried by a hyperpycnal flow, and immediately buried by fine grained sandstone. Sedimentological data suggest that Z. marambioensis sp. nov. lived in shallow-water environments, it seems possible that they were adapted to higher temperatures than other Recent species of the genus, which inhabit cold, deep marine environments. Fil: Palópolo, Evangelina Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Brezina, Soledad Silvana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Casadio, Silvio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Griffin, Miguel. Consejo Nacional de Investigaciones ...